Green Emission Carbon Quantum Dots from Lemon Juice for Selective Detection of Fe 3+ Ions - Pham Hung, Vuong; Thi Hoan, Bui; Dinh Tam, Phuong (VNU Journal of Science: Mathematics - Physics; Vol 35 No 1DO - 10.25073/2588-1124/vnumap.4317, 2019)
Abstract: In this article carbon quantum dots (Cdots) were prepared by a facile, green, economical hydrothermal method of the mixed deionized water and lemon juice. Optical and structural properties of the Cdots have been extensively studied by UV–visible and fluorescence spectroscopy, x-ray diffraction (XRD) techniques, and high-resolution TEM (HR-TEM). Surface functionality of Cdots has been illustrated by Fourier transform infrared spectroscopy (FTIR). The fabricated Cdots emit bright green light with a broad spectrum. The Cdots exhibit captivating sensitivity and selectivity toward Fe 3+ with a linear range from 0 to 80 ppm and a detection limit of 38.08 ppm. Keywords : Carbon quantum dots, lemon juice, sensing Fe 3+